Saudi Youth's Use of Social Networking Sites and Its Relationship to the Formation of Their Cultural Identity: A Field Study Applied to University Youth at King Faisal University (The International Journal of Educational Sciences and Arts, 2025)
This study aims to identify the reality of the spread of new media among members of Saudi society and its various means and what dimensions of this study. The study aims to use Saudi youth for social media sites and its relationship to the formation of cultural identity of young people at King Faisal University, as well as monitoring the reality of Saudi university youth's use of social media sites in general, Monitoring the reality of the use of Saudi university youth at King Faisal University (Sample study). This study belongs to the field of analytical descriptive studies that focus on Saudi youth's use of social media sites and its relationship to the formation of their cultural identity. The researcher conducted her study by applying to a sample of young university at King Faisal University which both have distinctive features that increase the richness of research and study, The study relied on applying a questionnaire form to a random sample of Saudi youth at King Faisal University. (350) Single to identify the impact of social media sites on their cultural identity.One of the most notable findings of the study is that there is no statistically significant correlation between sample members' exposure to social media sites. and their motivation from this exposure, and there are statistically significant differences in the positives that sample people see on social media sites according to their possession of more than one account on the sites And there are also statistically significant differences in the negatives perceived by members of the sample on social media sites according to their possession of more than one account on the sites, There are also statistically significant differences between specimen members of different demographic variables. (Type - level of study and rate of exposure to social media sites, there are no statistically significant differences between the demographic variables of the type - level of study and their tendencies towards the role of social media sites in shaping cultural identity. The study recommends that attention be paid to adolescents' socialization in which acts, ideas and values that would produce an individual who is a verifier of his or her identity are instilled or dispersed and closed to identity are instilled. It also recommends promoting different cultures at the Arab and global levels while maintaining the value line and conducting more studies on new media applications and its impact on young people.
Keywords: Saudi Youth; Social Media; Cultural Identity; University Students